Characterization of a Monoclonal Antibody Directed Against the Carboxyl-Terminus of Human Factor XIII - Song, Yeqing; Taubenfeld, Stephen M; Sheng, DeQuan; Matsueda, Gary R (Thrombosis and Haemostasis, 1994)
By deriving an anti-peptide monoclonal antibody, mAb 7A4, we characterized the relatively unstudied carboxyl-terminal end of the α-chain of human factor XIII, the plasma transglutaminase. MAb 7A4 was directed against the last eight amino acids (Gln-Ile-Gln-Arg-Arg-Pro-Ser-Met) and bound with a dissociation constant of 3.4 × 10−8 M. In a solid assay format, mAb 7A4 bound equally well to factor XIII obtained from human plasma, platelets or placenta. However, in a solution-phase assay format, the epitope was largely unavailable but could be readily exposed by heat denaturation. Tmmunoblotting showed that this epitope is conserved among all species of plasma factor XIII tested except rabbit suggesting that the carboxyl-terminus might be an important structural element. Other competitive binding experiments with synthetic peptides as inhibitors pointed toward the final carboxyl-terminal amino acid, Met-731, as an immunochemically important determinant. This was used advantageously to confirm the finding that the caiboxyl-leiminal Mel-731 is largely absent from placental factor XIII (1) as compared to platelet or plasma factor XIII.